Determinants of Agricultural Cooperative Performance Using Financial Ratio - Zelhuda, Shamsuddin (School of Business Innovation and Technopreneurship, Universiti Malaysia Perlis (UniMAP), 2018)
Link to publisher's homepage at http://ijbt.unimap.edu.my